ANALISIS PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN DI PROPINSI JAWA TENGAH DAN JAWA TIMUR - Sudarmadi .; Guntur Riyanto (Riset Manajemen dan Akuntansi, 2018)
The purpose of this research is to know the procedure of PNPM Mandiri Rural fund distribution in two regencies in Central Java region namely Sragen regency, Sukoharjo regency, while East Java region is represented by Madiun Regency and Ngawi Regency. Second year research objective: to find out whether PNPM Mandiri Rural needs to proceed and if continued what needs to be added. The research method used is quantitative research with data collection through questionnaire, indef interview, observation using area sampling and snowball sampling. The result of the research is the distribution procedure has been run well. The occurrence of irregularities due to difficult field conditions to meet the criteria of the program, the performance of UMKM beneficiaries both in Central Java and East Java became better than before and the performance of MSMEs in Central Java better than MSMEs in East Java after receiving business capital assistance from PNPM. PNPM Mandiri program should be resumed even with different names. Key words: Poverty, PNPM Mandiri